Handbook of research on the societal impact of digital media (Advances in media, entertainment, and the arts (AMEA) book series, 2016)
The Handbook of Research on the Societal Impact of Digital Media is an authoritative reference source for recent developments in the dynamic field of digital media. This timely publication provides an overview of technological developments in digital media and their myriad applications to literacy, education, and social settings